Chloride-induced corrosion and service life of reinforced concrete structures with Fusion Bonded Epoxy (FBE) coated steel rebars - Kamde, Deepak Kumar; Pillai, Radhakrishna G. (Research Data and Reports, 2026)
Numerous reinforced concrete (RC) structures have been constructed along the coastal region with significant chloride exposure and with a target service life of 100+ years.  In anticipation of achieving such long target service lives, the steel reinforcing bars (‘rebars,’ herein) in many of these structures are coated with Fusion-Bonded-Epoxy (FBE).  However, the FBE coated steel rebars are scratch damaged and exposed to sunlight/UV during transportation, storage, bending, and other construction activities.  These inadequate practices can adversely affect the corrosion of steel reinforcement; hence, chloride theshod and the service life of such steel‑coating-concrete systems. The practitioners tend to use existing test methods that are meant for uncoated steel rebars to test corrosion performance of coated rebars.  However, the results from such tests may lead to erroneous conclusions on the corrosion performance of coated rebars – highlighting a need for a suitable test method for FBE coated rebars in concrete.  In addition, the single-step chloride diffusion models used to estimate the service lives of RC systems with uncoated rebars may not be valid for coated rebar systems.  The degradation of coating and its characteristics must be accounted for service life estimations.  In short, this paper presents develops test methods, generate database on chloride threshold (Clth), and develop suitable service life estimation models for RC systems with FBE coated rebars, and with field practices in mind.